DEVELOPMENT OF JENGA GEOGRAPHY (JEGE) AS AN EVALUATION OF GEOGRAPHY MEDIA ON THE ATMOSPHERIC LAYER MATERIAL FOR CLASS X OF SMAN 71 JAKARTA - Kartika, Dewi; Handawati, Rayuna; Munandar , Aris (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
The study aims to determine the feasibility of developing a geography jenga game as an evaluation media for atmospheric layer material that can meet the dimensions of comprehensive evaluation competency. The study was conducted using a mixed method and the Plomp & Nieveen Educational Design Research research design model consisting of 3 stages, namely preliminary research, prototype stage, and assessment stage. The results of this study are the preparation of a Jenga Geography (JeGe) evaluation media with 88% material validity, 100% media validity, 90% validity from geography teachers, and the final stage of small group trials obtained 88% feasibility and large group trials obtained 90% feasibility. Thus, the results obtained by the Jenga Geography (JeGe) evaluation media as a whole obtained a very feasible feasibility category so that it can be used as a comprehensive evaluation media for atmospheric layer material. Keywords: Atmospheric Layers, Development, Educational Design Research Development, Jenga Game, Media Evaluation